Implicit motives in professional football and their concluded needs for coaching processes - Spreckels, C. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
Introduction Investigation showed that not only talent (Kang et al 2015) but certain personality traits could be predictive for a successful sports career (Kazén & Quirin 2018). As shown in other investigations confidence in success or fear of failure could be seen as states and not traits (Kazén, Kuhl & Quirin 2015). According to the Personality System Interaction Theory (PSI, Kuhl 2001) to hit the implicit motives support the confidence in success. Aim of this study was to explore if implicit motives of professional football players differ from the normal population and if certain clubs differ from others, so that it would a big point to coach them due to their individual personality. It also could be an explanation why certain coaches are successful within a certain club and others are not, because besides their football expertise their personality is matching. Methods N= 207 footballplayer of five clubs of the first and second league in Germany, aged 25 ± 7 years, were tested with the implicit personality test ViQ. This test includes the four main characters (worker, teamplayer, creative and dominant) as well as four motivational factors, which sums up to 16 different types. Comparing with the normal population of a mass media example (N= 24.000) and within different clubs the null hypothesis was, that the footballplayers don`t differ from normal population and within different clubs and the hypothesis according to this is that they differ. The chi²-Test was used for calculation. Results Results show that there is no significant difference from normal population to professional football players in the worker type ST (p=0,185) but differences in the three other types, TeamplayerType SF, Creative Type NF and Dominant Type NT, all significant (p<0,005). Differences between Clubs are also significant (p<0,005) within certain personality dimensions due to the PSI-Theory (Kuhl 2001). Conclusions Soccer coaches with their own combination of implicit motives should consider that their players may have different motives than other players in other clubs and themselves in order to be able to motivate them well, because the explicit motives have a directing effect and the implicit ones have an energizing effect, which determine the degree of motivation. Furthermore, it should be noted that this differs between clubs due to a specific club culture.